Limb body wall complex - Prasun Pankaj; Behera Bijaya; Pradhan Mandakini (Wolters Kluwer Medknow Publications, 2008)
Limb body wall complex (LBWC) is a rare clinicopathological entity, representing a compound anomaly pattern in ventral body wall defects. The authors report a case of LBWC diagnosed in early antenatal period. The pregnancy was terminated following the diagnosis. Fetal autopsy findings were typical of LBWC.